The role of second trimester uterine artery Doppler in pregnancies with systemic lupus erythematosus. (May 2015) - Pagani, Giorgio; Reggia, Rossella; Andreoli, Laura; Prefumo, Federico; Zatti, Sonia; Lojacono, Andrea; Tincani, Angela; Frusca, Tiziana
Abstract Objective The aim of this article is to assess the predictive value of second trimester mean uterine artery Doppler pulsatility index (mUtA PI) for pregnancy complications in women with systemic lupus erythematosus (SLE). Methods Cohort study of consecutive pregnancies complicated with SLE during a period of 12 years is used. SLE diagnosis was made before pregnancy. mUtA PI was measured between 23 + 0 and 26 + 6 weeks' gestation. Pregnancy and neonatal outcomes were collected. Small for gestational age (SGA) was defined as birth weight <10th percentile. Adverse pregnancy outcome (APO) was defined as one of the following: pre‐eclampsia (PE), SGA, placental abruption, stillbirth, or neonatal death. Differential diagnosis between PE and renal flare was made according to SLE‐disease activity index. Results There are 70 pregnancies in 64 women. PE was observed in four cases (6%), SGA in five cases (7%), and APO in seven cases (10%). mUtA PI showed a sensitivity and a specificity of 1.0 (95% CI 0.5–1.0) and 1.0 (95% CI 0.95–1.0) for PE, 0.40 (95% CI 0.12–0.77) and 0.97 (95% CI 0.89–0.99) for SGA, and 0.57 (95% CI 0.25–0.84) and 1.0 (95% CI 0.94–1.0) for APO, respectively. Conclusion Our findings suggest that uterine artery Doppler is confirmed to be a high sensitivity and a high specificity test for predicting PE even in SLE patients. © 2014 John Wiley & Sons, Ltd.